Factors influencing the intention to leave job among generation Z in information technology (IT) industry in Klang Valley - Sherlin, Marirasu (2020)
This study examines the factors that influence the intention to leave among generation Z in IT industries. Generation Z, who cannot be wedged at one working place, is the new emerging employees entering the workforce. High turnover rates may have negative impact on the organization, such as creating instability and uncertainty on labor conditions and rising human resource costs such as investment on training and recruitment. Therefore, this study analyzes salary satisfaction, job satisfaction, organizational commitment and organizational citizenship behavior towards employee’s outbound intention. It adopts a quantitative method where questionnaires were distributed to respondents using stratified random sampling. A total of 250 respondents participated in this study. Findings have shown that salary satisfaction, job satisfaction and organizational commitment have a negative relationship with intention to leave job except one variable which is organizational citizenship behavior. High intention to leave can result in low organization performance therefore retention strategies are proposed.